New deep-sea free-living marine nematodes from the Sea of Japan: the genera Siphonolaimus and Halichoanolaimus (Nematoda: Chromadorea) with keys to species identifications - Julia, Zograf; Yulia, Trebukhova; Olga, Pavlyuk (Zootaxa, 2015)
In deep-sea sediments from the Sea of Japan, two new species, Halichoanolaimus brandtae sp. n. and Siphonolaimus japonicus sp. n., were found and described. Siphonolaimus japonicus sp. n. is characterized by having short anterior sensillae, body length of 3670–4500 μm, buccal cavity with axial spear, and length of the spicules. Halichoanolaimus brandtae sp.n is characterized by the number of amphideal rings, long spicules, five precloacal supplements and by having a long cylindrical part of the tail. Keys to species level are provided.